Gastrointestinal bleeding risk of selective serotonin reuptake inhibitors by level of kidney function: A population‐based cohort study. (8th July 2018) - Iwagami, Masao; Tomlinson, Laurie A.; Mansfield, Kathryn E.; Douglas, Ian J.; Smeeth, Liam; Nitsch, Dorothea
Abstract : Aim: To estimate the risk of gastrointestinal (GI) bleeding associated with serotonin reuptake inhibitors (SSRIs) by level of kidney function. Methods: We conducted a cohort study using the Clinical Practice Research Datalink linked to Hospital Episode Statistics. We identified patients with chronic kidney disease (CKD; estimated glomerular filtration rate <60 ml min –1  1.73 m –2 for ≥3 months), and a comparison group of patients without it. Patients with CKD were further classified as stage 3a (eGFR 45–59 ml min –1  1.73 m –2 ), 3b (30–44 ml min –1  1.73 m –2 ) and 4/5 (<30 ml min –1  1.73 m –2 ). We excluded prevalent SSRI users at cohort entry. Exposure was time‐dependent SSRI prescription and outcome was first hospitalization for GI bleeding. We estimated adjusted rate ratio (aRR) and rate difference (aRD) of GI bleeding comparing periods with and without SSRI prescription at each level of kidney function. Results: The aRRs and aRDs were: (i) no CKD ( n  = 202 121) aRR: 1.66 (95%CI 1.37–2.01), aRD: 2.0/1000 person–years (5.5 vs . 3.5/1000 person–years in period with and without SSRIs); (ii) CKD stage 3a ( n  = 153 316) aRR: 1.86 (1.62–2.15), aRD: 4.2/1000 person–years (8.3 vs . 4.1/1000 person–years); (iii) CKD stage 3b ( n  = 46 482) aRR: 1.61 (1.27–2.04), aRD: 4.8/1000 person–years (9.9 vs . 5.1/1000 person–years); and (iv) CKD stage 4/5 ( n  = 11 197) aRR: 1.84 (1.14–2.96), aRD: 7.9/1000 person–years (15.3 vs . 7.4/1000 person–years). While there was no evidence of increase in the aRR ( P  = 0.922), there was strong evidence that the aRD increased as kidney function deteriorated ( P  = 0.001). Conclusions: While the relative risk was constant, the excess risk of GI bleeding associated with SSRIs markedly increased among patients with decreased kidney function.